2008
DOI: 10.1002/jor.20523
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of human chondrocytes during passaged monolayer cultivation

Abstract: Chondrocyte phenotype has been shown to dedifferentiate during passaged monolayer cultivation. Hence, we have investigated the expression profile of 27 chondrocyte-associated genes from both osteoarthritic cartilage tissue and healthy passaged human articular chondrocytes by quantitative real-time PCR. Our results indicate that the gene expression levels of matrix proteins and proteases in chondrocytes from monolayer culture decrease compared with those from cartilage tissue, while monolayer cultured chondrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
152
5
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(175 citation statements)
references
References 35 publications
16
152
5
2
Order By: Relevance
“…As a preliminary proof of concept, we additionally evaluated the expression profi les of passaged chondrocytes, a possible source for meniscal tissue engineering. Although this preliminary application involved cells derived from a single animal, our results were in agreement with the widely reported dedifferentiation of chondrocytes with passage; Col-2 rapidly decreased while Col-1 either increased continuously or stabilized after a certain number of passages (von der Mark et al, 1977;Darling and Athanasiou, 2005;Lin et al, 2008). However, the set of best predictors for passage number did not match the best set of tissue origin predictors.…”
Section: Me Levenston Et Al Discrimination Of Meniscal Cell Phenotypessupporting
confidence: 85%
See 1 more Smart Citation
“…As a preliminary proof of concept, we additionally evaluated the expression profi les of passaged chondrocytes, a possible source for meniscal tissue engineering. Although this preliminary application involved cells derived from a single animal, our results were in agreement with the widely reported dedifferentiation of chondrocytes with passage; Col-2 rapidly decreased while Col-1 either increased continuously or stabilized after a certain number of passages (von der Mark et al, 1977;Darling and Athanasiou, 2005;Lin et al, 2008). However, the set of best predictors for passage number did not match the best set of tissue origin predictors.…”
Section: Me Levenston Et Al Discrimination Of Meniscal Cell Phenotypessupporting
confidence: 85%
“…While the two ratios showed signifi cant difference between osteoarthritic and control cartilage tissues, only Col-1/ Col-2 seemed indicate dedifferentiation of chondrocytes with passage. Another approach to capture gene expression trends in dedifferentiation has involved statistical methods like clustering and principal component analysis (Lin et al, 2008). Although such approaches may be helpful in identifying groups of genes that behave similarly under certain conditions, they do not provide a clear quantitative marker that indicates cell phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to expand cells without standard passaging abolishes cell enzymatic trypsin exposure, which is directly associated with cellular dedifferentiation. NP cells are often compared to chondrocytes and, as such, several studies have shown the negative effects of passaging on chondrogenic gene expression (Darling et al, 2005;Lin et al, 2008). The rationale is that non-passaged cells do not need to waste time and energy on perhaps a poor re-differentiation process and, therefore, will be far more efficient in cell based therapy for tissue repair.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…where dedifferentiation decreases expression of collagen type II and aggrecan and increases expression of collagen type I (Darling et al, 2005;Lin et al, 2008). However, it is unclear if chondrocyte-like NP cells change in the same way during expansion (Kluba et al, 2005).…”
Section: Continuous Expansion Culture Of Np Cellsmentioning
confidence: 99%
See 1 more Smart Citation